Comparing the Outcomes of Lignocaine Spray and Solution in Reducing Pain and Discomfort During Flexible Nasopharyngolaryngoscopy - Parajuli, Ramesh; Limbu, Tilak Raj; Shakya, Abishesh (Journal of College of Medical Sciences-Nepal, 2025)
Background Flexible nasopharyngolaryngoscopy (NPL) is a vital diagnostic procedure in Otorhinolaryngology that is often associated with patient discomfort. Lignocaine, commonly used for topical anesthesia, is available in spray and solution forms, but evidence comparing their efficacy remains limited. This study compares the effectiveness and safety of lignocaine spray versus lignocaine solution in reducing pain and discomfort during flexible NPL. Methods A quasi-experimental, post-test only comparative study was conducted among 188 adult patients undergoing routine NPL at a tertiary hospital in Nepal. Participants were allocated into two groups based on their enrollment numbers: Group A received 10% lignocaine spray, and Group B received 4% lignocaine solution via cotton pledgets. Pain was assessed using a 100-mm Visual Analog Scale (VAS), and adverse effects (e.g., nasal pain and burning sensation, throat irritation and globus sensation, and unpleasant taste) were recorded immediately post-procedure. Results The mean VAS score was slightly lower in the spray group (28.04±14.26) than in the solution group (29.77±13.82); however, the difference was not statistically significant (p-value=0.401). Adverse effects occurred in 22.3% of participants overall, with a slightly higher incidence in the solution group (25.5%) than in the spray group (19.1%) (p-value=0.293). The most common adverse effects were nasal pain (9.0%), unpleasant taste (8.5%), and throat irritation (4.8%). No serious complications were reported. Conclusions Both lignocaine spray and solution offer comparable levels of comfort and safety during flexible NPL. Given the absence of significant differences in pain scores and adverse effects, either formulation may be chosen based on clinician preference, availability, and clinical context.